(untitled) - S Pascoe (Rome, 1997)
In this paper, the economic incentives to discard fish are examined. The effects of different management policies on these incentives are also investigated. The concept of an optimal level of discarding is discussed taking into account the externalities that can be created by discarding.
Keywords: fisheries,fishing